Freedom as critique. Foucault beyond anarchism - Schubert, Karsten (2020)
Abstract: Foucault’s theory of power and subjectification challenges common concepts of freedom in social philosophy and expands them through the concept of ‘freedom as critique’: Freedom can be defined as the capability to critically reflect upon one’s own subjectification, and the conditions of possibility for this critical capacity lie in political and social institutions. The article develops this concept through a critical discussion of the standard response by Foucault interpreters to the standard objection that Foucault’s thinking obscures freedom. The standard response interprets Foucault’s later works, especially The Subject and Power, as a solution to the problem of freedom. It is mistaken, because it conflates different concepts of freedom that are present in Foucault’s work. By differentiating these concepts, this article proposes a new institutionalist approach to solve the problem of freedom that breaks with the partly anarchist underpinnings of Foucault scholarship: As freedom as critique is not given, but itself a result of subjectification, it entails a demand for ‘modal robustness’ and must therefore be institutionalized. This approach helps to draw out the consequences of Foucault’s thinking on freedom for postfoundationalist democratic theory and the general social-philosophical discussion about freedom